Developing Worked Examples to Strengthen Mathematical Communication Skills in Teaching Statistics - Bertha Oktavika Sembiring; Sugiman Sugiman (Didaktik Matematika, 2025)
Mathematical communication skills are an essential part of mathematics learning; however, numerous studies have found that students' abilities in this area remain at a low to moderate level across various mathematical topics. This study aims to design and present worked examples that support mathematical communication skills, particularly in the context of measures of central tendency and data dispersion. This study employed a Research and Development approach, utilizing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The participants consisted of five Year 8 students who had not yet studied the topic. Data were collected through open-ended interviews, paper-based tests, and expert validation sheets. The developed worked examples were validated by three experts based on content, construction, and linguistic criteria. The validation results indicated that the worked example met both face and logical validity criteria. The ADDIE cycle was completed after the Evaluation stage, during which the result of the limited trials showed that more than 80% students achieved the minimum score in solving the paired problem. These findings indicated that worked examples designed with self-explanation prompts and contextual variations can facilitate students' mathematical communication skills, especially in understanding and expressing mathematical ideas through multiple representations